Efetividade de vídeos psicoeducativos na resolução de conflitos e satisfação conjugal - Renata Campos Moreira de Souza Coelho (2019)
Literature indicates that the ability to build and maintain satisfactory marital relationships is essential for mental and psychosocial health. “Marital relationship" has been widely studied in the last 50 years. However, the study of educational programs that help couples improve their relationships is still insipid in Brazil. The objective of this study is to study the implications of psychoeducational videos on the level of marital satisfaction and conflict resolution, considering that many studies associate the prediction of changes in the improvement of marital quality to marital education programs. To do this, we divided the research into two moments: the first part consists of a literature review on online and face-to-face psychoeducational interventions for couples, while the second involves an empirical research that evaluated the effects of a psychoeducational program denominated "Well Married Project", through videos on conflict, affection, and marital satisfaction. We used a systematic electronic search of articles published from 2009 until January 2019 using the MEDLINE, LILACS, IBECS, Index Psychology, BDENF and State Department of Health in SP, PsycINFO, and Cochrane Library databases to reach the objectives of the first study. In the end, we selected twelve studies from 1682 and divided them between the online (one study) and face-to-face (eleven studies) modalities of the programs for couples, which were later categorized based on objectives and procedures. The results indicated immediate improvements in the quality of the marital relationship after using the intervention programs. The second study included pre and post-test stages to evaluate the level of marital satisfaction and conflicts of the participants submitted to the psychoeducation program. The differential was the focus on the Brazilian cultural specificities and the complete performance of the interventions on virtual platforms. The research consisted of 163 adults, married or living together with a minimum of six months. The participants filled a sociodemographic and marital quality questionnaire and were submitted to three different types of scales measuring the marital satisfaction, conflict, and affection: CRBQ (Conflict Resolution Behavior Questionnaire), CSS (Conjugal Satisfaction Scale), and Familiogram. Moreover, we transmitted 21 videos divided into three blocks, during three sessions. The results indicated improvements in the quality of the marital relationship and the levels of agreement among the postintervention couples in fifteen of the twenty-four possible measures, from low to moderate levels. We formulated the hypothesis regarding the effectiveness of such programs, contributing for the research in the field when enlightening new tendencies concerning the psychological interventions from the cross data of both studies, given that the virtual platforms can provide a wider reach.